2023
DOI: 10.1177/17423953231184220
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 deficiency in long-term metformin treated type 2 diabetic patients: Prevalence and risk factors in a Tunisian population

Abstract: Objectives: To determine the prevalence of vitamin B12 deficiency in a Tunisian population with type 2 diabetes (T2D) on metformin treatment for more than three years and to identify its risk factors. Methods: This is a cross-sectional study conducted on 257 patients with T2D treated with metformin for at least three years. Patients were divided into two groups according to their vitamin B12 status. Low vitamin B12 was defined as ≤ 203 pg/mL. Results: The mean age of the patients was 59.8  ±  7.9 years. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The use of mostly over-the-counter vitamin B12 supplementation by FDS2 participants was low (<4%) and not significantly different by serum vitamin B12 status, suggesting that this was not a confounding factor. Although consistent with most previous studies, [9][10][11][12][13][14][15][16] we found no evidence that metformin therapy was associated with DSPN, whether through vitamin B12 deficiency or other mechanisms, there was a graded relationship between metformin dose category and both vitamin B12 deficiency and anaemia that was independent of confounding factors in our participants. Such a dose-response relationship has been found previously for serum vitamin B12 deficiency, 1 especially daily doses ≥2000 mg, but the association between metformin therapy and anaemia is less clear.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The use of mostly over-the-counter vitamin B12 supplementation by FDS2 participants was low (<4%) and not significantly different by serum vitamin B12 status, suggesting that this was not a confounding factor. Although consistent with most previous studies, [9][10][11][12][13][14][15][16] we found no evidence that metformin therapy was associated with DSPN, whether through vitamin B12 deficiency or other mechanisms, there was a graded relationship between metformin dose category and both vitamin B12 deficiency and anaemia that was independent of confounding factors in our participants. Such a dose-response relationship has been found previously for serum vitamin B12 deficiency, 1 especially daily doses ≥2000 mg, but the association between metformin therapy and anaemia is less clear.…”
Section: Discussionsupporting
confidence: 91%
“…Although some of our participants with a total vitamin B12 <200 pmol/L had an active B12 >35 pmol/L and were thus not categorised as deficient, this is below the 7.4-28.8% range in published studies employing a similar <200 pmol/L total serum vitamin B12 concentration cut point. 5,6,14,16 In a developed country such as Australia, greater nutritional sources likely counteract metformin-associated vitamin B12 malabsorption (and the additional potential influence of PPI use) compared to the situation in the developing world where the highest rates of metformin-associated deficiency have been reported. 14,16 As a corollary to this, vitamin B12 deficiency severe enough to cause DSPN and/or megaloblastic anaemia is (as in the present study) likely to be relatively rare in Australia compared with other countries.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations